Spatial distribution and ecological niche modelling of Triplochiton scleroxylon K. Schum., in the Guineo-Congolese region of Benin (West Africa) - TOKO IMOROU, ISMAÏLA (My University, 2020)
Triplochiton scleroxylon (samba) is a West and Central African forest species of high socio-economic value which is increasingly threatened by anthropogenic pressures from various sources. The aims of this study is to determine the Triplochiton scleroxylon spatial distribution pattern and the potential impact of climate change on the distribution of habitats in the Guineo-Congolese region of Benin. All of 2311 occurrence data of this species were combined with current and future climate variables in the Maxent program under RCP scenarios 4.5 and 8.5 by 2055. Analysis of the spatial pattern of Triplochiton scleroxylon revealed an aggregative distribution between 1m and 7 m distance. But for a distance between 0 and 1 m and more than 7 m, the spatial pattern revealed a random spatial distribution. Under current climatic conditions, 45.17 % of the study area of the Guineo-Congolese region in Benin and 61.69 % of the one of protected areas are currently very suitable for the cultivation and conservation of samba. Projections to 2055 indicate a significant increase in the area of these habitats for the two scenarios used. These results show that the current and future climatic conditions of the Guineo-Congolese region in Benin remain favourable for the cultivation and conservation of this species. Unfortunately, outside protected areas, these favourable habitats are occupied by settlements and fields. Taking these results into account could effectively contribute to the sustainable conservation of this species in Benin.
Keywords: Maxent; ecological niche; climate change; aggregative distribution; Triplochiton scleroxylon; Benin.